Relación entre las Instituciones informales y el bienestar subjetivo: Un análisis basado en microdatos alrededor del mundo durante el periodo 2017-2022. - Sanmartín López, Jessica Soledad (2025)
Subjective well-being is a key component of human development, influenced by informal institutions such as trust, social norms, and economic values. Despite their significance, empirical studies on their impact remain limited, hindering the design of effective public policies aimed at enhancing well-being through the strengthening of informal institutions. This research aims to analyze the relationship between informal institutions and subjective well-being across countries using microdata from the seventh wave of the World Values Survey. Discrete choice econometric models and multilevel analysis were employed to identify key patterns and trends. The results demonstrate that societies with higher levels of trust, face-to-face social networks, and shared economic values exhibit a significantly greater probability of improved well-being. Furthermore, multilevel models revealed that these effects vary across countries, with stronger impacts observed in contexts characterized by greater institutional development. Consequently, it is suggested that public policies should prioritize fostering interpersonal trust and reinforcing inclusive social norms, while accounting for institutional differences between countries. Context-specific strategies are essential to maximize the positive influence of informal institutions on societal well-being.